PERBEDAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DAN MODEL PEMBELAJARAN SELF DIRECTED LEARNING TERHADAP HASIL BELAJAR PAI DAN BP SISWA KELAS X JURUSAN TEKNIK MESIN SMK NEGERI 5 PADANG - Hakim, Abd; Nurdin, Syafruddin; Fitriza, Rozi (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2024)
ABSTRACT ABD. HAKIM, NIM 2220010006 Thesis "Differences between Project Based Learning and Self Directed Learning Models on PAI and BP Learning Outcomes for Class X Students of Mechanical Engineering Department of SMK Negeri 5 Padang". Postgraduate Islamic Religious Education Study Program at UIN Imam Bonjol Padang. This research is motivated by the low learning outcomes achieved by students. It can be seen that the learning process is less than optimal, so that an active, creative and meaningful learning process has not yet been realized, where during the learning process the teacher is still using learning that is not yet relevant. This research discusses the differences between the Project Based Learning learning model and the Self Directed Learning learning model on PAI and BP learning outcomes for class X students of the Mechanical Engineering Department at SMK Negeri 5 Padang. This research uses a quantitative experimental design method, randomized control group posttest only design by applying the Project Based Learning learning model in the experimental class in class X.1, totaling 36 people and the control class in class X.2, totaling 36 people. The instrument used by researchers was a test of learning outcomes on the material The Role of Ulama Figures in the Spread of Islam in Indonesia (Method of Islamic Da'wah by Wali Songo in Java). Research data on student learning outcomes was collected through a learning outcomes test with 20 objective questions, then analyzed using SPSS version 20. The findings from this research were that there were differences in PAI and BP learning outcomes on the material on the Role of Ulama Figures in the Spread of Islam in Indonesia (Da'wah Method Islam Wali Songo in Tanah Java) Class This is proven based on the results of the analysis, it is found that t count > t table, namely 3.957 > 2.028, so Ha is accepted and Ho is rejected.